Audit Tata Kelola Teknologi Informasi Menggunakan Framework Cobit 5 Pada Pt. Bisma Tunas Jaya Sentral - Devanti, Khairunnisa; Parwita, Wayan Gede Suka; Sandika, I Kadek Budi (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2019)
Abstract PT. Bisma Tunas Jaya Sentral is a company engaged in the sale of finished goods (especially motorcycles), spare parts, and motorcycle service specifically for the Yamaha brand. To support business services, IT services in the form of software and hardware are used in business processes.To ensure optimal IT management, measurements of the level of IT governance that have been carried out and compare it with the level expected by management. This measurement refers to the COBIT domain 5. The steps of this study start from research planning, design of data collection instruments, data collection and data processing to conduct a final evaluation that results in recommendations for improved management in accordance with the maturity of the COBIT model.The results of data processing that have been carried out indicate that the IT infrastructure management method that is already running at PT Bisma Tunas Jaya is not good enough. It is proven by the high gap between the current management level and the level desired by management.